Interactive English E-Learning Based on Cloud Speech-to-Text API - Andi Nurkholis; Renda Bimantara; Neneng Neneng (Universitas Trunojoyo Madura, 2022)
Good English skills will be a competitive asset in the world of work and education. Mastery of English is essential to be prepared early on. Schools allocate study time and learn how to use textbooks, which sometimes makes students bored and bored. Students are expected to be more motivated in learning and practicing English language skills. So we need a suggestion for other learning media that is more applicable. This study aims to develop mobile interactive e-learning media based on Cloud Speech-To-Text API at PGRI Pasir Sakti vocational high school. The method used is adopting the waterfall type system development life cycle. The material feasibility test was carried out based on expert validation by two English teachers, which resulted in an agreed category. Meanwhile, the ISO 25010 standard testing covers four aspects: functional suitability, performance efficiency, portability, and usability, which resulted in strongly agreed categories.